A The Effect of Using Fly Ash and Chemical Additive on The Bearing Capacity of Soil-Cement: Pengaruh Penggunaan Fly Ash dan Chemical Additive Terhadap Daya Dukung Soil-Cement - M. Sazili Harnawansyah; Mahmuda; Alif Muhammad Bintang; Muhammad Rizki (PILAR, 2023)
Soil is a place to grow and develop living things, both flora and fauna on this earth. In addition, land is also an important component for infrastructure development such as roads, dams, and other buildings. Over time, the population density is growing rapidly. The more the population grows, the less land available but more and more buildings to be erected. Due to the reduced available land, the buildings that were erected were made soaring. The higher the building, the greater the value of the bearing capacity of the soil that must support the load. Therefore, research is needed on soil stabilization with variations of fly ash, variations of cement and Chemical Additives in order to get a good soil bearing capacity value. In this study, the physical and mechanical properties of the soil on clay from Sungai Rengit Village, Banyuasin were tested by adding a mixture of fly ash + DIFA SS 2.5% to obtain the optimum level of fly ash in fly ash-soil. After getting the optimum level of fly ash, the addition of cement + DIFA SS 2.5% was added to get a good soil bearing capacity value. The results of this study indicate that the greater the addition of cement + optimum fly ash 12.5% ​​+ DIFA SS 2.5% in soil-cement, the better the value of the soil bearing capacity.